Popularization of Science in Brazil: getting onto the public agenda, but how? - Tait Lima, Márcia; das Neves, Ednalva Felix; Dagnino, Renato (Journal of science communication, 2008)
The importance the Brazilian government has given in the last few years to the dissemination of science points out the necessity of a more discerning analysis about the establishment of this subject on the public agenda and the related public policies undertaken. This work tries to contribute to the debate as an inquiry about the policies to popularize and disseminate Science and Technology (S&T) established by the Science and Technology Popularization and Dissemination Department, which was created in 2004. In order to do so, theoretical references from Public Policy Analysis, the Studies of Science, Technology and Society (SSTS), and Public Communication of Science are used. Furthermore, we analyze some of the results from research on Science and Technology Understanding carried out in Brazil in 2006. As a final point, this associated approach aims at identifying some of the limiting factors related to science dissemination actions in Brazil.